(untitled) (Italian Journal of Public Health, 2011)
Problems in health care systems are present on a planetary scale due to a discrepancy between scarce resources and vast needs. These are mainly generated by the aging of the population. Everywhere in the world, state health care agencies simply reduce the quantity and eventually the quality of available services. This approach is unacceptable, at least in Europe, where health care is a legal right, granted from birth to death. This paper departs from the poor support available nowadays for clinical research and the trivial investments on prevention, and hypothesizes a new approach based on clinical research and prevention which, in the long term, would generate a just, efficient, sustainable health care system stemming from patients’ needs. This is discussed from various viewpoints. It emerges that there is a need to switch the focus of health systems away from cures towards prevention and as well as a need for better translational research. It is of note that in France such a program based on clinical research and prevention was launched in 2008